Legal and Ethical Dimensions of Islamic Microfinance in Poverty Alleviation: A Critical Analysis - Olaitan Abdulkabir Oladapo (ORGANIZE: Journal of Economics, Management and Finance, 2024)
According to the World Bank’s (2019) study, poverty accounts for more than 70% of the total population in Nigeria, implying that over 130 million people in the country, live in poverty. This pathetic situation is further aggravated by financial exclusion whereby low-income people are neglected away from the financial system because they are considered uneconomical to serve or too difficult to reach. According to the World Bank’s Global Findex, 1.7 billion adults globally are financially excluded, living without formal credit or savings (FINCA International, 2024).  Recently, microfinance has emerged as an important instrument of poverty alleviation in the developing countries with more than 7000 micro lending institutions providing loans to more than 25 million poor individuals across the world (Dahiru and Hassan, 2008). Despite the number of microfinance banks in Nigeria with over 800 of them in the country, Microfinance banks’ contribution to Nigeria’s economy is less than 1% (National Bureau of Statistics (NBS), 2020). The question now is, where lies the problem? Through a doctrinal approach, it is observed that the system of operation and management of Microfinance banks in Nigeria has eroded their primary objective (financial inclusion). This is mainly due to the imposition of high interest rate by Microfinance Institutions, poor risk management mechanism, weak organizational structure, insufficient capital, shortage of experts, among others. With its success in some parts of Nigeria such as Al-Barakah Microfinance Bank in Lagos state, Islamic microfinance is recommended to be the real solution in achieving financial inclusion through its products that are interest-free and customer-friendly to the poor and middle-class citizens, in a bid to ensure optimum poverty alleviation in a well regulated and ethical business environment.